Response of Alnus glutinosa to Phytophthora bark infections at ambient and elevated CO2 levels - Macháčová, Markéta; Tomášková, Ivana; Corcobado, Tamara; Nagy, Zoltan; Milanović, Slobodan; Janoušek, Josef; Pešková, Vítězslava; Čepl, Jaroslav; Gezan, Salvador; Nakládal, Oto; Zumr, Václav; Kalyniukova, Alina; et al. (Frontiers in Forests and Global Change, 2024)
Mortality of the riparian alder population caused by Phytophthora pathogens has been studied for over 20 years throughout Europe, recently gaining more importance in the context of evident climate change. The main objective of this study was to examine the pathogenicity of species from the "Phytophthora alni complex" present in the Czech Republic (P. ×alni and P. uniformis) and P. plurivora to Alnus glutinosa seedlings grown at ambient and elevated CO2 concentration. An underbark inoculation test was performed with seedlings grown from seeds collected from two Czech alder populations, one suffering from severe Phytophthora decline and the other disease-free. The results showed significant differences in lesion development and seedling mortality. After a 13-week experimental period, at both CO2 levels P. ×alni and P. uniformis showed high aggressiveness to A. glutinosa seedlings causing lesions of variable sizes and mortality of 33.3 %, and 45.8 % of plants, respectively. In contrast, P. plurivora did not cause mortality to any plant, and lesion sizes did not differ significantly from those in control plants. Physiological measurements did not reveal any significant differences between Phytophthora species except for plants inoculated with P. plurivora showing increased values in specific physiological parameters four weeks post-inoculation. Net photosynthesis decreased over the measurement period in all treatments with significant differences Naformátováno: Mezera Před: 0 b. found between measurements conducted two and four weeks after the inoculation. Transpiration showed a decreasing trend in all inoculated plants with no significant differences between Phytophthora species at both CO2 levels. Chemical analyses of root samples showed high variability in sugars and phenolic compounds related to the plant's health status. This is the first study to examine the response of alder seedlings to Phytophthora pathogens at different CO2 levels. The findings demonstrate high aggressiveness of P. ×alni and P. uniformis and weaker aggressiveness of P. plurivora to alder seedlings regardless of the CO2 level.